Leiomyosarcoma of small intestine.: Six new cases. - Praderi, José; Bermúdez Belbussi, Jorge; Abascal, Winston; Falchetti, Juan; Armand Ugon, Alfredo (Cirugía del Uruguay, 1985)
Six patients with leiomyosarcoma of small intestina are reportad.